Автоматизоване керування технологічним комплексом виробництва пива на основі сценарно-цільового підходу - Власенко, Л. О.; Місюра, М. Д.; Ладанюк, А. П.; Кишенько, В. Д.; Vlasenko, L.; Misyura, M.; Ladanyuk, A.; Kishenko, V. (КНТУ, 2013)
Наведено результати проведення системного аналізу на основі сценарно-цільового підходу для технологічного комплексу (ТК) виробництва пива. В результаті роботи розроблені А- та С-сценарії, проведено імітаційне моделювання за допомогою апарату прографів. The improving the efficiency of TC beer production from scriptwriting-targeted approach. The results of system analysis for beer production technical complex on the base of scenario-oriented approach are given. The results of work are A- and C-scenarios are developed and simulation was conducted with the help of prograf set. Conducted in three phases systematic analysis of TC beer production from scriptwriting-purpose approach proved the feasibility and necessity of its use. In the first phase TC is described by A script that provides: the links between technological elements that are its members, and their impact on the situation arising, the second stage is it (a script) specification in the base and prografs and tabular analysis of the behavior of TC under different conditions, the third stage is the implementation developed efficient algorithms based management conducted a systematic analysis of modern information technology and the use of various intellectual mechanisms by C-script. The result is to increase the efficiency of TC brewing industry and reduce the time to make the right decisions.
Automated management of complex technical production of beer on the basis of a scenario-oriented approach
Keywords: системний аналіз; сценарно-цільовий підхід; прографи; А-сценарій; С-сценарій; прогнозування; коригуючі дії; systems analysis; scenario-oriented approach; prograf; A-scenarios; C-scenarios; forecasting; corrective action